The effect of current ratio, debt to equity ratio, return on asset, and earning per share on stock prices in property and real estate companies listed on the idx year 2017-2020 - Puspita Sari; Rahmawati Rahmawati; Helmiati Helmiati (Jurnal Riset Manajemen Indonesia, 2022)
The research was conducted with the aim to examine the effect of CR, DER, ROA, and EPS on stock prices in property and real estate companies listed on the Indonesia stock exchange in 2017-2020. The population in this study were all property and real estate companies listed on the indonesian stock exchange. The technique used in sampling is purposive sampling method, the samples in this study were selected as many as 15 companies. Hypothesis testing using multiple linear regression with the help of SPSS 26.00 for windows. Based on the test results simultaneous the variables CR, DER, ROA, and EPS proved to have a significant effect on stock prices in property and real estate companies listed on the Indonesian stock exchange in 2017-2020. Partially, ROA has no effect on stock prices. The close relationship that occours between the variables CR, DER, ROA, and EPS on stock prices is very strong with a correlation coefficient value (R) of 83,6%. While the contributin of the independent variable to the dependent variable is 67,6%, the remaining 32,4% is explained by other variables that are not include in this research model.